China's "National Spatial Infrastructure" and global governance: Chinese way of Military–Civil Fusion (MCF) over the ocean. (3rd July 2021) - Masuo, Chisako T.
ABSTRACT: China is constructing an overwhelming satellite network, called the "National Spatial Infrastructure", that might change the security and economic operations of global governance. Xi Jinping's Military–Civil Fusion (MCF) strategy is founded on this system. Along with the well-known BeiDou Navigation Satellite System (BDS), the remote sensing satellite system and the communication and broadcasting satellite system form this new infrastructure. China is using it to establish a strong monitoring capability by: collecting various data on vessels' navigation and oceanography; developing a huge communication network that covers actors and objects on the ocean as well as in the sky and the space; reforming its fishery administration and establishing new laws that enable the authorities to mobilise the numerous Chinese fishermen operating in global waters; and cultivating people-friendly apps to invite more users into the Chinese systems. Based on its strong victimhood mentality that calls for "great rejuvenation of the Chinese nation", the Xi Jinping administration is trying to initiate a new human age by developing advanced technology and integrating it with social implementation that aims to increase China's influence over the globe.